ZUR FÖRDERUNG DER INDIVIDUELLEN MEHRSPRACHIGKEIT DES FREMDSPRACHENLERNENDEN – AUFGABEN FÜR DIE POLNISCH- UND DIE FREMDSPRACHENLEHRENDEN - Hinc, Jolanta (Neofilolog, 2019)
This paper relates to the concept of didactics of multilingualism. The didactics of multilingualism is geared towards promoting the language awareness of pupils and showing that knowing more languages makes the learning process more efficient. This can be realized by comparing grammar structures, comparing vocabulary, discussing sociocultural aspects or taking advantage of the intercomprehension. The aspect of the negative transfer should be also captured by showing the interference fields and discussing the interference errors. The didactics of multilingualism should be understood as a continuous process that begins with the acquisition of the mother tongue and goes further over the acquiring the first foreign language and the next foreign language. Following this, the didactics of multilingualism should involve tasks for teachers of the Polish language and teachers of the first, second and next foreign languages.